2015
DOI: 10.1111/cod.12338
|View full text |Cite
|
Sign up to set email alerts
|

Acute irritant bullous contact dermatitis caused by Euphorbia helioscopia

Abstract: References1 Wilken K, Schempp C M. Toxic phytodermatitis caused by Euphorbia helioscopia L. (sun spurge). Hautarzt 2005: 56: 955-957. 2 Barla A, Birman H, KültürŞ, Öksüz S. Secondary metabolites from Euphorbia helioscopia and their vasodepressor activity. Turk J Chem 2006: 30: 325-332. 3 Schmidt R J, Evans F J. Skin irritants of the sun spurge (Euphorbia helioscopia L.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Although MI is reported to cause a flare in preexisting oral lichen planus, 11 there are no previously reported cases of MI/MCI causing de novo lichenoid contact dermatitis as far as the authors are aware at the time of submission. Pirmez et al 12 recently reported 3 confirmed and 27 suspected cases of photoaggravated allergic contact dermatitis secondary to MI/MCI, but none had any lichenoid features histologically.…”
Section: Discussionmentioning
confidence: 97%
“…Although MI is reported to cause a flare in preexisting oral lichen planus, 11 there are no previously reported cases of MI/MCI causing de novo lichenoid contact dermatitis as far as the authors are aware at the time of submission. Pirmez et al 12 recently reported 3 confirmed and 27 suspected cases of photoaggravated allergic contact dermatitis secondary to MI/MCI, but none had any lichenoid features histologically.…”
Section: Discussionmentioning
confidence: 97%
“…It is traditionally used to treat skin cancers, actinic keratosis, and digestive system disorders . Many species of Euphorbia typically have a milky sap that can cause irritant reactions, including E. helioscopia , E. pulcherrima , E. marginata , E. myrsinites , and E. hermentiana . E. trigona , known as African milk tree, also produces a milky sap which causes irritant contact dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…This contact leads to a reaction on the skin called irritant contact dermatitis (ICD) and allergic contact dermatitis (ACD) 3 . Only a few case reports have been reported with contact dermatitis by Euphorbia helioscopia (EH) in the literature [4], [5]. In this case report we want to share our experience with EH contact dermatitis in ED.…”
Section: Introductionmentioning
confidence: 98%